Simply your expression
4[(12-2) ²÷4]
1 answer:
Answer:
100
Step-by-step explanation:
Simplify the following:
4 (12 - 2)^2/4
Hint: | Express 4 (12 - 2)^2/4 as a single fraction.
4 (12 - 2)^2/4 = (4 (12 - 2)^2)/4:
(4 (12 - 2)^2)/4
Hint: | Cancel common terms in the numerator and denominator of (4 (12 - 2)^2)/4.
(4 (12 - 2)^2)/4 = 4/4×(12 - 2)^2 = (12 - 2)^2:
(12 - 2)^2
Hint: | Subtract 2 from 12.
| 1 | 2
- | | 2
| 1 | 0:
10^2
Hint: | Evaluate 10^2.
| 1 | 0
× | 1 | 0
| 0 | 0
1 | 0 | 0
1 | 0 | 0:
Answer: 100
You might be interested in
I think it’s 557
reasoning in pic
Answer:
(2.4, -1)
Step-by-step explanation:
Using midpoint formula plug in the info (x1+x2)/2, (y1+y2)/2
Answer:
y=3x-2 is a function because it passes the vertical line test.
Step-by-step explanation:
Answer:
3(2+x)=0
Step-by-step explanation:
<u>Here are some vocab words:</u>
Product: Multiplication
Sum: Addition
"A number": x
3(2+x)=0
Answer:
C
Step-by-step explanation:
(x,y) = p + t(a)
(x,y) = (-1,6) + t(3,-1)
(x,y) - (-1,6) = t(3,-1)
(x + 1, y - 6) = t(3, -1)